Kepercayaan sebagai Anteseden Perilaku Inovatif di Tempat Kerja - Efawati, Yen (Asosiasi Ahli Administrasi Indonesia, 2023)
This study aims to analyze the factors determining individual innovative workplace behavior. Trust as an antecedent of innovative behavior mediated by knowledge sharing. The approach uses a quantitative approach with 120 respondents from 60 Muslim fashion industries in Indonesia. Hierarchical multiple regression analysis approaches were applied to test the research model. The analysis found that trust values ​​significantly influence individual innovation behavior, which is mediated by knowledge sharing. This research highlights the influential role of promoting individual innovation behavior in management practices. It is shown that mutual trust between subordinates and coworkers needs to be improved. Also, openness and sustainable learning can be developed to improve individual innovation capabilities.